2008
DOI: 10.1007/s11661-008-9616-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Phase Transformations and Their Effects on Ferritic Weld Residual Stresses with X-Rays and Neutrons

Abstract: Abstract. Weld residual stresses often approach, or exceed, the yield strength of the material, with serious implications for the integrity of engineering structures. It is not always feasible to measure residual stresses, so integrity assessments often rely heavily on numerical models. In ferritic steels, the credibility of such models depends on their ability to account for solid-state phase transformations that can have a controlling effect on the final residual stress state. Furthermore, a better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 17 publications
(24 reference statements)
5
94
0
Order By: Relevance
“…In-situ synchrotron diffraction is a suitable technique to study these solid-state phase transformations. [11][12][13][14][15][16][17] Dutta et al observed that loading conditions below the yield strength of austenite lead to elastic strains upon martensitic transformation and M s increases with an increase in the applied external tensile load. [18] From a thermodynamic point of view, a reduction in Gibbs free energy of a system indicates whether it is favorable for phase transformations to take place.…”
Section: Introductionmentioning
confidence: 99%
“…In-situ synchrotron diffraction is a suitable technique to study these solid-state phase transformations. [11][12][13][14][15][16][17] Dutta et al observed that loading conditions below the yield strength of austenite lead to elastic strains upon martensitic transformation and M s increases with an increase in the applied external tensile load. [18] From a thermodynamic point of view, a reduction in Gibbs free energy of a system indicates whether it is favorable for phase transformations to take place.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the material will experience a partial austenitization, in which the perlite and some ferrite The interpretation of the stress distributions in the weld region based on microstructures is complicated by the fact that the residual stresses must have a contribution of shrinkage, sudden cooling of surface and phase transformation, and in the case of pipes due to geometry, being a balance of all contributions over the weld section. Thus, according Dai et al 46 , the stresses distribution may not be explained solely in terms of the local transformation temperature in the weld regions.…”
Section: Microstructure Analysismentioning
confidence: 99%
“…According Dai et al 46 , at high temperatures, the strains are accommodated by inelastic deformation of the material, and the stress supported by the component follows the yield strength of the material. However, when the component is cooling, the transformation takes place, the transformation strains, as well as any associated transformation plasticity, act to reduce the tensile strains, which can even reverse sign.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But it was not until the 1990s [6] that the high flux and penetrating power of synchrotron x-rays allowed the investigation of residual strains and stresses at the micron scale. In the last 20 years the subject has advanced apace, moving to higher energies such that strains can be probed, even in steels 25 mm thick, at the 100 micron scale [7] and shorter timescales (milliseconds) so that, for example, changes occurring during weld cooling [8] can be studied, not just the final welded residual stress state. The advent of new synchrotron facilities across the world, and particularly the development of materials engineering capabilities at the new UK Diamond Light Source at Harwell, make it particularly timely for the Journal of Strain Analysis for Engineering Design to invite some of the leading researchers in the field to contribute to a special issue on Strain Measurement by Synchrotron X-ray Diffraction.…”
mentioning
confidence: 99%